(untitled) (Asian Journal of Medical and Biological Research, 2021)
Air pollution is a major challenge worldwide, particularly in the developing world. This study aimed to revelation people’s perceptions regarding the impacts of air pollution on reproductive health. This study was conducted among107 respondents and a google form was used to create a survey questionnaire. Purposive sampling has been used to select the respondents. A large number of respondents are male and aged less than 30 years. A large number of respondents are from the urban area and depends on Non-Government Job. A satisfactory number of the respondents know about air pollution. Both male and female respondents know smoke inhalation during pregnancy, damage reproductive organs of the male, birth defects due to air pollutions, and delayed brain development of the newborn baby. Most of the respondents gather their knowledge from television and social media. Asian J. Med. Biol. Res. 2021, 7 (2), 147-152